A critical review on rural youth unemployment in Ethiopia - Fuad Mohammed Shuker; Hakim Hashim Sadik (International Journal of Adolescence and Youth)
Rural youth unemployment is a major challenge in Ethiopia that threatens its economic development. Most young people rely on subsistence farming for livelihoods, but land availability is declining due to population growth and fragmentation of plots. High underemployment and landlessness deprive many youths of work. Rural infrastructure is underdeveloped, hindering transportation and market access. Additionally, rural youth lack financial access to start businesses, leading to insignificant job creation in rural areas. As a result, many youths migrate internally to cities or abroad in search of work. Unless the government implements effective policies to address obstacles like landlessness, poor infrastructure, financial exclusion and lack of rural job opportunities, developmental problems will likely continue worsening in Ethiopia. Development depends on resolving rural youth unemployment.